Asymmetric synthesis of N,O,O,O-tetra-acetyl d-lyxo-phytosphingosine, jaspine B (pachastrissamine), 2-epi-jaspine B, and deoxoprosophylline via lithium amide conjugate addition. - Abraham, E; Brock, E; Candela-Lena, J; Davies, S; Georgiou, M; Nicholson, R; Perkins, J; Roberts, P; Russell, A; Sánchez-Fernández, E; Scott, P; Smith, A; et al. (2008)
The highly diastereoselective anti-aminohydroxylation of (E)-gamma-tri-iso-propylsilyloxy-alpha,beta-unsaturated esters, via conjugate addition of lithium (S)-N-benzyl-N-(alpha-methylbenzyl)amide and subsequent in situ enolate oxidation with (+)-(camphorsulfonyl)oxaziridine, has been used as the key step in the asymmetric synthesis of N,O,O,O-tetra-acetyl d-lyxo-phytosphingosine (20% yield over 7 steps), the anhydrophytosphingosine jaspine B (10% yield over 9 steps), 2-epi-jaspine B (14% yield over 9 steps), and the Prosopis alkaloid deoxoprosophylline (26% yield over 7 steps).